Epidemic Spread and Its Management Through Governance and Leadership Response Influencing the Arising Challenges Around COVID-19 in Pakistan—A Lesson Learnt for Low Income Countries With Limited Resource - Nawaz, Ahsan; Su, Xing; Barkat, Muhammad Qasim; Asghar, Sana; Asad, Ali; Basit, Farwa; Iqbal, Shahid; Zahoor, Hafiz; Raheel Shah, Syyed Adnan (Frontiers in Public Health, 2020)
The corona virus disease (COVID-19) was first time reported in the China (Wuhan) at the end of the year 2019. It has rapidly spread over 216 countries including the USA, UK, Europe, Russia and many Asian countries. It has affected more than 4.5 million people, and around 0.3 million deaths have been reported globally. Many preventive measures have been adopted worldwide to mitigate its spread. The Government of Pakistan has also taken many preventive measures to combat COVID-19 outbreak, such as: rapid response by good governance, continuous monitoring of the pandemic spread in the affected areas, and the integration of resources from multiple sectors including health, education, defense, and the media. According to global statistics, the number of COVID-19 cases in the country remained remarkably lower than the expected number for the first 84 days, as compared to other countries. The study finds that strict adherence to national policies, effective governance and unity at national level resulted in better outcomes. Hence, preventive measures, rapid responses, strategies adopted for combating the challenges, and controlled epidemic spread in the country may be adopted as a learning tool to exterminate corona virus in other countries having similar work scenarios and financial constraints.